Cost-effectiveness of vector control for supplementing mass drug administration for eliminating lymphatic filariasis in India. - Donald S Shepard; Aung K Lwin; Sunish I Pulikkottil; Mariapillai Kalimuthu; Natarajan Arunachalam; Brij K Tyagi; Graham B White (PLoS Neglected Tropical Diseases, 2024)
Background/methodology Despite progress using mass drug administration (MDA), lymphatic filariasis (LF) remains a major public health issue in India. Vector control could potentially augment MDA towards LF elimination. We conducted a cost-effectiveness analysis of MDA alone and MDA together with vector control single (VCS) modality or vector control integrated (VCI) modalities. Data came from historical controls and a three-arm cluster randomized trial of 36 villages at risk of LF transmission in Tamil Nadu, India. The arms were: MDA alone (the standard of care); MDA plus VCS (expanded polystyrene beads covering the water surface in wells and cesspits to suppress the filariasis vector mosquito Culex quinquefasciatus); and MDA plus VCI (VCS plus insecticidal pyrethroid-impregnated curtains [over windows, doors, and eaves). Economic costs in 2010 US$ combined government and community inputs from household to state levels. Outcomes were controlled microfilaria prevalence (MfP) and antigen prevalence (AgP) to conventional elimination targets (MfP<1% or AgP<2%) from 2010 to 2013, and modeled disability adjusted life years (DALYs) averted. Principal findings The estimated annual economic cost per resident was US$0.53 for MDA alone, US$1.02 for VCS, and US$1.83 for VCI. With MDA offered in all arms, all arms reduced LF prevalence substantially from 2010 to 2013. MDA proved highly cost effective at $112 per DALY averted, a very small (8%) share of India's then per capita Gross Domestic Product. Progress towards elimination was comparable across all three study arms. Conclusions The well-functioning MDA program proved effective and very cost-effective for eliminating LF, leaving little scope for further improvement. Supplementary vector control demonstrated no statistically significant additional benefit on MfP or AgP in this trial.